2021
DOI: 10.1200/jco.21.00334
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab Versus Gemcitabine or Pegylated Liposomal Doxorubicin for Patients With Platinum-Resistant Ovarian Cancer: Open-Label, Randomized Trial in Japan (NINJA)

Abstract: PURPOSE This phase III, multicenter, randomized, open-label study investigated the efficacy and safety of nivolumab versus chemotherapy (gemcitabine [GEM] or pegylated liposomal doxorubicin [PLD]) in patients with platinum-resistant ovarian cancer. MATERIALS AND METHODS Eligible patients had platinum-resistant epithelial ovarian cancer, received ≤ 1 regimen after diagnosis of resistance, and had an Eastern Cooperative Oncology Group performance score of ≤ 1. Patients were randomly assigned 1:1 to nivolumab (24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
89
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 40 publications
5
89
0
4
Order By: Relevance
“…Subgroup analysis demonstrated a numerically longer overall survival with nivolumab compared with chemotherapy among patients with OCCC. 27 , 28 Taken together, these findings suggest that ICI monotherapy can induce responses in only a small subset of patients with OCCC. Several studies have proposed that PARP inhibitors can induce immunogenic tumor cell death, increase tumor neoantigens, upregulate PD-L1 expression, and, therefore, enhance the response to ICIs.…”
Section: Discussionmentioning
confidence: 83%
“…Subgroup analysis demonstrated a numerically longer overall survival with nivolumab compared with chemotherapy among patients with OCCC. 27 , 28 Taken together, these findings suggest that ICI monotherapy can induce responses in only a small subset of patients with OCCC. Several studies have proposed that PARP inhibitors can induce immunogenic tumor cell death, increase tumor neoantigens, upregulate PD-L1 expression, and, therefore, enhance the response to ICIs.…”
Section: Discussionmentioning
confidence: 83%
“…The results revealed an active response in platinum-sensitive patients, but the response in platinum-resistant patients was still low, and no benefit was observed compared to the previous trial UMIN000005714. Nivolumab was also evaluated in comparison with gemcitabine or pegylated liposomal doxorubucin (PLD) for the treatment of platinum-resistant OC, but no treatment benefit in terms of improved overall survival was observed (JapicCTI-153004) ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Current trials evaluating the use of ICIs in ovarian cancer have not demonstrated improved survival [ 45 , 46 ]. Combination therapies with ICIs, chemotherapy regimens, PI3K/mTORC1/2 inhibitor [ 39 , 43 ], tyrosine kinase inhibitors [ 41 , 42 ], and/or PARP inhibitors [ 47 ] may be indicated for the treatment of advanced or relapsed OCCC.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapies with ICIs, chemotherapy regimens, PI3K/mTORC1/2 inhibitor [ 39 , 43 ], tyrosine kinase inhibitors [ 41 , 42 ], and/or PARP inhibitors [ 47 ] may be indicated for the treatment of advanced or relapsed OCCC. To date, there have been no positive correlations reported between treatment response and potential biomarkers related to the PI3K/mTOR or PD-1/PD-L1 pathways [ 44 , 45 , 46 ]. Hence, our stricter PFI criterion of grading platinum sensitivity for OCCC may be recommended for post-treatment surveillance.…”
Section: Discussionmentioning
confidence: 99%